Experimental investigation of water flow window system and numerical modeling of solar thermal energy storage with phase change materials on the way of nearly zero energy buildings - Yamac, Halil Ibrahim; Koca, Ahmet (Elsevier, 2021)
Latent heat storage of Phase Change Material (PCM) is beneficial for Thermal Energy Storage (TES) in solar energy systems. The Water Flow Window (WFW) is a concept that has emerged in the last decade. The circulation of water between glazing dissipates and stores solar-based energy. These two concepts can be brought together on the way of Nearly Zero Energy Buildings. In this study, the experimental investigation of the WFW system and numerical modeling of solar TES with PCM as a heat exchanger has been carried out. The experimental study is performed under environmental conditions like prototype testing. Two equivalent testing cabinets with WFW and standard (air-filled) window are employed to compare the electrical energy consumption of the cooling devices of testing cabinets. Two different PCM, filled in tubes as a pistol type, is mounted in a water tank. The TES tank volume is 5.675 liters (42% water, 46% RT28 HC, 12% RT35 HC). The windows' surface area is approximately 0.3 m(2). Results show that the consumption ratio of cooling devices can fall under 85% and 2916 kJ energy can be stored throughout 6 h. Visualization of the melting process in the TES tank is obtained with the numerical study.
Keywords: Solar energy; Water flow window; Thermal energy storage; Phase change material; Nearly zero energy buildings